A new single-phase two-wire hybrid active power filter using extension p-q theorem for photovoltaic application - Tan, Perng Chen; Salam, Zainal (IEEE, 2004)
This paper presents a new single-phase two-wire hybrid active power filter configuration that interconnects a passive high-pass filter in parallel with an active power filter and a photovoltaic system. The proposed configuration can improves the filtering performance of the conventional active power filter, as well as simultaneously supply the power from the photovoltaic arrays to the load and utility. Furthermore, the derivation of arrays to the load and utility. Furthermore, the derivation of extension p-q theorem. This paper describes the proposed hybrid active power filter with photovoltaic system. It primarily focuses on the power circuit control system and the compensation current reference derivation. The proposed system effectively filters harmonics under 1 kHz but also higher frequency to achieve wideband harmonics compensation. The THD of source current is reduced from 76.83 % to 3.21 %. The simulation results that verify the theoretical predictions of the proposed configuration is presented.